2022
DOI: 10.1016/j.imu.2021.100842
|View full text |Cite
|
Sign up to set email alerts
|

UNAS-Net: A deep convolutional neural network for predicting Covid-19 severity

Abstract: We present a study on Covid-19 detection using deep learning algorithms that help predict and detect Covid-19. Chest X-ray images were used as the input dataset to prepare and train the proposed model. In this context, deep learning architecture (DLA) and optimisation strategies have been proposed and explored to support the automated detection of Covid-19. A model based on a convolutional neural network was proposed to extract features of images for the feature-learning phase. Data augmentation and fine-tunin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…f t controls the information of memory cells from time t−1 to time t. It controls the input information to the memory cells at time t. o t controls the information of the memory cells at time t until the hidden state h t . Equations ( 17), (18), and (19), respectively show the formulation of f t , i t , and o t in the LSTM network.…”
Section: Pandemic Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…f t controls the information of memory cells from time t−1 to time t. It controls the input information to the memory cells at time t. o t controls the information of the memory cells at time t until the hidden state h t . Equations ( 17), (18), and (19), respectively show the formulation of f t , i t , and o t in the LSTM network.…”
Section: Pandemic Predictionmentioning
confidence: 99%
“…In this study, DNN‐based methods are proposed for the diagnosis of COVID‐19. In Reference 19, a deep learning architecture is proposed to predict the cases of COVID‐19 in India. In this research, combined CNN + LSTM have been used to predict COVID‐19.…”
Section: Related Workmentioning
confidence: 99%
“…Mangalmurti and Wattanapongsakorn 35 described effective ML approaches for the automatic detection/classification of COVID‐19 and other lung diseases. Syarif et al 36 employed DL to detect COVID‐19. The model recommended using CXR.…”
Section: Preliminariesmentioning
confidence: 99%
“…Jha et al, [12] reported 90% efficiency for COVID-19 CXR images segmentation in a datasets from Kaggle and GitHub [13,14] with the multilevel threshold value of 75, 145, 185, 195 and 230 respectively, and the algorithm used is Falcon speed based Adaptive opposition Slime mould Algorithm (FS-AOSMA) with the falcon speed of 0.05 to 1 m/sec. Abdusy Syarif et al, [15] applied Otsu thresholding to binarize 12,467 CXR images, and archived the classification of 97.36% accuracy and 95.24% sensitivity by using Universitas National Network (UNAS-Net) deep learning model.…”
Section: Introductionmentioning
confidence: 99%